PELATIHAN CNC ROUTER UNTUK BUMDES DESA HEUBEULISUK - Engkos Koswara; Nasim (Universitas Majalengka, 2021)
Heubeulisuk Village is a village located in Argapuran District, Majalengka Regency. Similar to other villages, this village has a Village Owned Enterprise (BUMDes). One of the activities of the BUMDes is the production of wooden wall clocks and several other crafts made of acrylic material. Wood Size craftsmen until now only use a simple cutting saw to make the craft and acrylic using a hand drill. The chainsaws facilitated by the local village government are not as sophisticated as imagined. With the BUMDes CNC Router machine, it is able to increase the amount of production and minimize the production time required. In this service program scheme, training on the use of CNC Routers for BUMDes Heubeulisuk will be carried out starting assembling, preparing cutting/chiseling tools, making CAD models, CNC controllers to execution/feeding of workpieces.